Cougar kill rates and prey selection in a multiple‐prey system in northeast Oregon. Issue 7 (13th August 2014) - Clark, Darren A.; Davidson, Gregory A.; Johnson, Bruce K.; Anthony, Robert G.
ABSTRACT Cougars (Puma concolor) are a primary predator of mule deer (Odocoileus hemionus) and elk (Cervus elaphus) throughout western North America. Effective management of predator‐prey systems requires a solid understanding of kill rates, prey use, and selection. We implemented a 3‐year study in northeast Oregon to investigate cougar diet, kill rates, and prey selection in a multiple‐prey system to assess the degree to which patterns in cougar predation may be generalizable across systems and to identify selective predation patterns of cougars that may affect ungulate populations. We marked 25 adult cougars with global positioning system (GPS) collars and monitored predation sequences for 7, 642 days to identify kill sites. In field investigation of kill sites, we identified remains of 1, 213 prey items killed by cougars, of which 1, 158 (95.4%) were native ungulates. On average, cougars killed 1.03 ungulates/week (95% CI = 0.92–1.14), but kill rates varied by season, sex, and reproductive status of cougars. Cougars killed ungulate prey 1.55 (95% CI = 1.47–1.66) times more frequently during summer (May–Oct) than winter (Nov–Apr). Kill rates were higher in summer because juvenile ungulates were the most frequently killed prey item and were smaller than prey killed in winter. Female cougars with kittens >6 months old killed prey more frequently than males, solitary females, and females with kittens <6 months old likely in response to the increased energetic burden of raising kittens. Male cougars killed larger prey than females, which likely explains why males killed at similar rates as solitary females, despite the larger body size of males. We documented patterns in prey selection influenced by season and demographic classification of cougars. Diets of male cougars included roughly equal amounts of elk (52.2%) and deer (47.8%), whereas diets of females were dominated by deer (74.6%). Male and female cougars displayed strong patterns of selection for elk calves during summer. During winter, female cougars selected deer fawns and males selected elk calves. Female cougars with kittens >6 months old demonstrated little selection for any age class or species of prey, highlighting an opportunistic foraging strategy to maximize energy gains while feeding young. Across all cougars, we observed a pattern of selection for adult male deer during winter but not summer and did not observe patterns of selection for adult elk according to sex. Our results strongly supported the hypothesis proposed by [Knopff et al. (2010) Journal of Wildlife Management, 74: 1435–1447] that cougar predation is influenced by season and demographic classifications of cougars and our results provide strong evidence that this hypothesis should be generalizable to other areas. The patterns of selection for juvenile elk and deer suggested wildlife managers should consider the potential negative effects of cougars on ungulate populations in areas where juvenile recruitment has been chronically low. © 2014 The Wildlife Society.